Excessive daytime sleepiness and its determinants: do they have a pattern with study semesters among postgraduate medical resident doctors? - H. S., Siddalingaiah; Chaudhuri, Aditi; D., Chandrakala; Singh, Amarjeet (International Journal Of Community Medicine And Public Health, 2017)
Background: Residency is a stressful period in the career of a medical professional. Excessive daytime sleepiness (EDS) is a major problem among resident doctors due to long work hours, stress, sleep deprivation, shift work, lack of sleep hygiene and other lifestyle related factors. The sleep problems and related factors need to be studied among resident doctors to know if any cumulative effect exists. Methods: A cross sectional study design with pre-validated sleep assessment proforma, Epworth sleepiness scale (ESS), and sleep hygiene index (SHI) as study tools which were self-administered among a total of 428 enrolled eligible resident doctors. Results: A total of 350 resident doctors returned the filled proforma, ESS and SHI (response rate 81.7%). Prevalence of EDS was found to be highest in 2nd (51.1%), 3rd (55.2%) and 5th (47.1%) semesters. Socio-demographic factors did not vary much across semesters except for slight increase in quantity of coffee/tea intake. No major changes in shift pattern, total sleep hours were found across semesters but work hours differed significantly. Sleep latency was least in 3rd semester where EDS was highest. Similarly, sleep quality, sleep hygiene and weekly sleep hours were least in 2nd and 3rd semester where EDS prevalence was high. In addition, as per visual analogue scale ratings by resident doctors, those in 2nd and 3rd semesters were maximally tired and maximally sleepy which is consistent with the finding of high prevalence of EDS in these semesters as recorded by ESS. Conclusions: Sleep quality, sleep quantity, sleep hygiene and weekly work hours emerged as important and sensitive predictors of EDS across study semesters. These components must be present in any intervention package to address EDS especially in the first three semesters of residency program and other similar occupational settings.